COMPARATIVE ANALYSIS OF THE FINANCIAL STATEMENTS BASED ON PROFITABILITY AND SOLVENCY RATIO - Cakra Wibawa Khoiril Fadli; Anna Sulistyawati; Rita Listiyanti; Sri Hermuningsih (ZILLZELL MEDIA PRIMA, 2023)
This research aims to determine the comparative analysis of financial statements. PT Semen Indonesia (Persero) Tbk with PT Indocement Tunggal Prakarsa Tbk. Based on the results of analysis of profitability and solvency ratios. This type of research data uses secondary data. Data collection techniques are based on literature and documentation from several journals and financial reports. Analysis The data used is profitability ratio analysis consisting of Return on Assets (ROA) and Return On Equity (ROE). Then the solvency ratios are Total Debt To Equity Ratio and Total Debt To Total Asset Ratio. The research results show that PT Indocement Tunggal Prakarsa Tbk has a higher level of ability to obtain net profit after tax from the total assets it owns. PT Indocement Tunggal Prakarsa has a higher level of ability to obtain net profit after tax from the total equity it owns when compared to PT Semen Indonesia (Persero) Tbk. Based on the calculation results of the analysis, it can be seen that the Debt Equity On Ratio (DER) value of the two companies, it can be concluded that PT Indocement Tunggal Prakarsa Tbk has a lower level of debt risk when compared to PT Semen Indonesia (Persero) Tbk. Then, if we look at the Debt to Assets Ratio (DAR) analysis value, PT Indocement Tunggal Prakarsa Tbk has a lower level of debt risk when compared to PT Semen Indonesia (Persero) Tbk.